What should be offered to Mr.Chamanlal? - Ratol, Jasdeep (IJRDO- Journal of Educational Research, 2019)
Mr.Chamanlal, along with his family wants to visit wildlife in the state of Madhya Pradesh, India. Basically, he is from Delhi and having disposable income of 50,000 Rs. for this planned tour. He is working as a Public Relation Officer in a private company and now he is having vacations from his office. He has no idea about wildlife itinerary and his problem is from where to start and how to start for this wildlife tour? He wishes to visit National parks within MP state. Mr.Chamanlal wants to start his tour on Saturday night and finishes by Monday. The question that remains unanswered is what should be offered to Mr. Chamanlal?